The roles of social support and coping style in the relationship between gratitude and well-being. (January 2016) - Lin, Chih-Che
Abstract: This study aimed at examining the roles of social support and coping style in the relationship between gratitude and well-being. Seven hundred and fifty Taiwanese college students ranging in age from 18 to 22 years completed measures of gratitude, social support, coping style, and well-being. Structural equation modeling showed partial mediation effects of social support and coping style between gratitude and well-being. Moreover, a multi-group analysis found that females with higher levels of social support tended to use more active coping strategies when encountering a problem compared to their male counterparts. Implications for future research and limitations of the present findings are discussed. Highlights: Gratitude has significantly positive effects on well-being. Social support partially mediated the association between gratitude and well-being. Active coping partially mediated the association between gratitude and well-being. Gratitude influences well-being through social support and coping style differently across males and females.